Bhil kills - Varma, S. C. (Delhi, 1978)
Little do people know that among the tribal communities of India, the incidence of homicide is the highest among the Bhils. In a small area of 4,500 square kilometers covering 2 predominantly Bhil districts of Jhabua and Dhar in Madhya Pradesh, every 32nd hour, one Bhil is killing the other. Almost all the killings are intra-community. Notwithstanding the killings, the Bhils are by no means cral They do not kill with a criminal iment but of jealousy, passion, quick and unpredictable temper and to avenge their honour and self-respect. The Bhils constitute the second largest tribal group in India. Only the Gonds exceed them in number. The Bhils are a very colourful tribe; brave, virile and extremely daring. They still believe in and practise the system of marriage by capture. This book takes a close look at the Bhil culture and gives an account of 100 actual killings among them.